2019
DOI: 10.3390/en12101920
|View full text |Cite
|
Sign up to set email alerts
|

Algal Biofuels: Current Status and Key Challenges

Abstract: The current fossil fuel reserves are not sufficient to meet the increasing demand and very soon will become exhausted. Pollution, global warming, and inflated oil prices have led the quest for renewable energy sources. Algal biofuels represent a potential source of renewable energy. Algae, as the third generation feedstock, are suitable for biodiesel and bioethanol production due to their quick growth, excellent biomass yield, and high lipid and carbohydrate contents. With their huge potential, algae are expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
77
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(79 citation statements)
references
References 169 publications
(167 reference statements)
1
77
0
1
Order By: Relevance
“…On the other hand, recent researches to improve the cost of obtaining microalgae has focused on the use of waste and integrating the co-production of high-value compounds [39]. CO 2 sequestration using a biorefinery approach, through interconnection with the cultivation of microalgae, is an interesting idea, since the waste generated from power plants or other industrial facilities is used [34,40].…”
Section: Of 19mentioning
confidence: 99%
“…On the other hand, recent researches to improve the cost of obtaining microalgae has focused on the use of waste and integrating the co-production of high-value compounds [39]. CO 2 sequestration using a biorefinery approach, through interconnection with the cultivation of microalgae, is an interesting idea, since the waste generated from power plants or other industrial facilities is used [34,40].…”
Section: Of 19mentioning
confidence: 99%
“…Because of their fast growth rate, low nutrient requirements, and high lipid contents, microalgae have immense potential as biological sources to produce biofuels, high-value biomolecules, and feeds [1][2][3][4]. Unfortunately, at present, the energy requirements and costs of microalgae-based commodities are still relatively high, which hinders their broad commercialization [5][6][7]. Recently, several studies have reported that cultivating microalgae as biofilm (where cells are attached to a solid surface) can substantially reduce energy requirement and enhance economic feasibility of microalgae-based biorefineries, owing to the high photosynthetic efficiency, high biomass productivity, 2 of 10 and low cost of harvesting [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…By definition a renewable resource, biomass remains an important aspect of the search for sustainable energy sources [1]. This includes not only refuse and energetic wood plantations, but also specially grown algae [2]. Algae-derived biomass may be used for energy production, whether by simple firing or co-firing with refuse-derived fuels, other biomass, or non-renewable fuels, or through production of biofuels [3].…”
Section: Introductionmentioning
confidence: 99%